Water Inrush Mechanism in Fault Fracture Zone Based on a Nonlinear Mechanical Model of Three Flow Fields - Hou Dian-chen; Su Xiao-jian; Wang Wen-qiang; Du Feng; Zhao Yu-yao (Geofluids)
Water inrush in the working face caused by seepage instability of fault fracture zone is a major disaster which threatens the safety production in a coal mine. Based on the principle of fluid mechanics, a nonlinear mechanical model with three flow fields is established in this paper. Combining with the actual situation of a fault fracture zone in a coal mine, a multicoupled numerical model is built in COMSOL Multiphysics, in order to study the water pressure and flow velocity in the three flow fields and the flow state of fluids in the aquifer and fault under different ratios of fault permeability and aquifer permeability. The research results show that the permeability in the fault fracture zone is an essential factor affecting the danger of water inrush, and the pressure and flow velocity in the boundary zone of the adjacent flow field varies significantly. Besides, the water inrush in the fault fracture zone is a gradual dynamic process, and the fluid flow from the aquifer through the fault gradually changes from a linear flow state into a nonlinear flow state. Meanwhile, the non-Darcy effect increases and decreases with the growth and decrease of the permeability in the fault fracture zone.